Simultaneous diazinon removal and toxicity reduction from real wastewater using a starch-assisted CuCoFe2O4 magnetic MOF-5 composite derived from fish-scale biochar - Weifan Lin; Danling Guo; Weijiang Gou; Yuzheng Yan; Shizhao Ren; Weifeng Tang; Bifan Lin; Fuxing Lin (Journal of Environmental Management, 2026)

SiGSTU18 positively regulates saline-alkali tolerance in foxtail millet through glutathione metabolism and glutamic acid-mediated alleviation of oxidative stress and ion toxicity - Yun Li; Yuxue Zhao; Fuxing Xiang; Fangying Chen; Yanrui Xu; Xiaohu Lin; Jihan Cui; Yucui Han (Plant Science, 2026)

Fluoride and lead abatement from synthetic and industrial wastewaters using magnetic biochar composite of walnut shell/CuFe2O4/MIL-101(Al) - Fuxing Lin; Jiaye Li; Zihao Chen; Xuncheng Huang; Weifan Lin (Journal of Environmental Management, 2025)

ETDformer: an effective transformer block for segmentation of intracranial hemorrhage - Wanyuan Gong; Yanmin Luo; Fuxing Yang; Huabiao Zhou; Zhongwei Lin; Chi Cai; Youcao Lin; Junyan Chen (Medical & Biological Engineering & Computing, 2025)

Bisphenol AF induces cell cycle arrest and apoptosis in TM3 Leydig cells via the p53 signaling pathway - Chenlu Li; Haolong Luo; Mengyuan Chen; Fuxing Lin; Xiangmei Ren; Yefei Huang; Li Zhou (Reproductive Toxicology, 2025)

Predicting the potential distribution of major marine mammals in the Cosmonaut Sea - Yufei Dai; Fanyi Meng; Fuxing Wu; Xing Miao; Denghui Yan; Mingding Zhong; Shunan Cao; Yuli Wei; Longshan Lin (Frontiers in Marine Science, 2025)
The Southern Ocean, a critical marine region on Earth, is undergoing significant environmental changes due to global climate change, including reductions in sea ice extent, ocean acidification, and alterations in the Antarctic Circumpolar Current (ACC). The Cosmonaut Sea, notable for its dynamic sea ice and rich biological activity, remains one of the least explored regions in the Southern Ocean, with limited data on its marine mammal populations. This study conducted during the 38th Chinese National Antarctic Research Expedition (CHINARE) from January to March 2022, collected systematic data on marine mammal occurrences. Species distribution modeling (SDM) was used to assess the influence of environmental variables on the distribution of the most abundant marine mammal species observed in the Cosmonaut Sea, including humpback whales ( Megaptera novaeangliae ), crabeater seals ( Lobodon carcinophaga ), and Antarctic minke whales ( Balaenoptera bonaerensis ). Our results indicated significant performance variations among the different algorithms, with ensemble model yielding more accurate predictions. Environmental variables such as water depth, sea surface height, and mixed layer thickness were identified as significant factors influencing habitat suitability for different species. Humpback whales were found to have the widest distribution range, followed by Antarctic minke whales and crabeater seals. Generally, the study provides the first comprehensive analysis of marine mammal distribution in the Cosmonaut Sea, highlighting the effectiveness of ensemble models in ecological predictions. The findings emphasize the importance of integrating high-resolution data and incorporating predator-prey interactions in future studies to improve our understanding and conservation of these complex ecosystems.

Proposal, process development, and multi-aspect investigation of a novel environmentally friendly multigeneration process in arrangement with a sea water desalination unit - Fuxing Lin; Jianhua Wang; Tirumala Uday Kumar Nutakki; Mohamed Ayadi; Sayed Fayaz Ahmad; Taseer Muhammad; Chuang Lui (Journal of Environmental Chemical Engineering, 2023)

Reply to “Misuse of molecular tools results in misleading dates for the ancestor of the Indo‐Pacific humpback dolphin” by Chen - Liyuan Zhao; Watchara Sakornwimon; Wenzhi Lin; Peijun Zhang; Rachawadee Chantra; Yufei Dai; Reyilamu Aierken; Fuxing Wu; Songhai Li; Kongkiat Kittiwattanawong; Xianyan Wang (Marine Mammal Science, 2022)